2011
DOI: 10.1002/pssa.201026757
|View full text |Cite
|
Sign up to set email alerts
|

Resistive memory switching in layered oxides: AnBnO3n+2 perovskite derivatives and Bi2Sr2CaCu2O8+δ high‐Tc superconductor

Abstract: Resistive memory switching was investigated in titanates and niobates of the type AnBnO3n+2 and in the high‐Tc superconductor Bi2Sr2CaCu2O8+δ. We studied the switching by current injection perpendicular to the layers. Both dc and pulsed measurements were performed. Out‐of‐plane transport properties were investigated by measurements of the resistance and current–voltage characteristics (IVs) vs. temperature for different resistive states. The critical temperature of superconducting transition and the critical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 57 publications
7
38
0
Order By: Relevance
“…In case of cuprates, physical doping may be persistent at low temperatures in a sense that it is relaxing very slowly after removing the light [17,18] or field [21,[23][24][25]. Recently, a persistent electric doping via strong current injection was discovered [24,25]. It is resembling a resistive switching phenomenon in memristor devices [26,27] and is related to previous similar observations in point contact experiments on Bi 2 Sr 2 CaCu 2 O 8+x (Bi-2212) [23].…”
Section: Introductionsupporting
confidence: 69%
See 4 more Smart Citations
“…In case of cuprates, physical doping may be persistent at low temperatures in a sense that it is relaxing very slowly after removing the light [17,18] or field [21,[23][24][25]. Recently, a persistent electric doping via strong current injection was discovered [24,25]. It is resembling a resistive switching phenomenon in memristor devices [26,27] and is related to previous similar observations in point contact experiments on Bi 2 Sr 2 CaCu 2 O 8+x (Bi-2212) [23].…”
Section: Introductionsupporting
confidence: 69%
“…Koval et.al. [25] demonstrated that a short-pulse doping strategy leads to highly reversible and reproducible doping, similar to resistive switching in point contacts [23]. This is probably related to the lack of significant electromigration during the short pulse, which may eventually lead to an irreversible destruction of the crystal structure [21].…”
Section: Short-pulse Dopingmentioning
confidence: 95%
See 3 more Smart Citations